On coastal circulation modeling - Camerlengo, Alejandro; Nasir Saadon, Mohd. (Malaysian Journal of Science, 1996)
This paper reviews the implementation of a generalÂized vertical coordinate system leading to a a vertical coordinate system for the ocean. The theoretical framework, of a new techÂnique that splits the barotropic and baroclinic modes is discussed.